Using the Spherical-Radial Model during Filtration of Non-Newtonian Oils - Qiyasli, N.I.; Dadashzadeh, M.A. (Herald of Azerbaijan Engineering Academy, 2024)
Various models are utilized in exploring recently discovered deposits, tailored to the deposit's thickness. These models are pivotal in calculating bed parameters, including reservoir permeability, well production, and pressure distribution. The widespread adoption of modeling involves partially preserving physical processes, allowing adaptability to different parameters and theory modifications. Continuous model enhancement contributes to improved information integrity, providing a more accurate representation of reality. Models are crucial for problem-solving, starting with foundational aspects and subsequently incorporating specific parameters. The development of models employs diverse algorithms, serving as a generalized method to address practical challenges and express the mathematical requirements for engineers.